PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Wahab, Abdul (Students Journal of Accounting and Banking, 2012)
The companys main objective is to enhance shareholder value through increased prosperity or shareholders. Prosperity shareholders will increase if the share price held up well. In this case, financial management plays an important role in order to maximize shareholder wealth. This study aims to, analyze the influence of the companys performance as intervening variables that mediate the effect of capital structure on firm value in the LQ-45 group companies in Indonesia Stock Exchange. The sample is a company listed on the Indonesia Stock Exchange (IDX) the LQ-45 from 2008 through 2010, in accordance with the criteria established and acquired as many as 19 companies. This study uses path analysis (path analysis) to determine the effect of the performance of the company as an intervening variable that mediates the effect of capital structure on firm value. The results show a negative effect of capital structure and significant impact on firm performance and corporate value. Performance of the company is not able to mediate the effects of capital structure on firm value. Â Keywords: capital structure, firm performance, firm value